Hemodynamic Effects of Intravenous Administration of Olprinone Hydrochloride on Experimental Pulmonary Hypertension - Kakura, Hideaki; Miyahara, Kenkichi; Amitani, Shigeru; Sohara, Hiroshi; Koga, Masaaki; Sakamoto, Hiroshi; Misumi, Kazuhiro; Miura, Naoki (Arzneimittelforschung, 2000)
To examine acute effects of olprinone hydrochloride (CAS 106730-54-0, Coretec®) on pulmonary hypertension, hypoxic pulmonary hypertension was produced in 6 adult Beagle dogs. Using this pulmonary hypertension model, single intravenous bolus injections of olprinone at doses of 10, 30 and 100 µg/kg were administered at 5-min intervals and hemodynamic parameters were evaluated.Heart rate increased at doses of 30 and 100 µg/kg, but did not change at a dose of 10 µg/kg. Mean aortic pressure, mean pulmonary arterial pressure, pulmonary vascular resistance and systemic vascular resistance and right ventricular stroke work index did not change at doses of 10 and 30 µg/kg, but they decreased significantly at a dose of 100 µg/kg. On the other hand, cardiac index and the first derivative value of the left ventricular pressure did not show significant change at all doses.These results indicate the vasodilating effects on peripheral and pulmonary vessels in hypoxic model at high doses of olprinone. Its application in right heart failure accompanied by pulmonary hypertension therefore is expected to yield promising results.
Keywords: CAS 106730-54-0; Coretec®; Olprinone, dog, effect on pulmonary hypertension, hemodynamic effects; Phosphodiesterase 3 inhibitors